Syntax Analysis Directed by Transition and Action Table - Dovedan Han, Zdravko (Array, 2005)
A definition is given of the deterministic syntax analysis method applicable on all context-free and context languages, especially suitable for the machine processing. Syntax analysis method rests on the definition of the language, known as the "language with properties", that needs to be implemented. The basic for the language with properties definition is a generator (automata) and not the grammar.